Federal Research Investment and Innovation in Information Technology: A Virtuous Cycle. - Hennessy, John (Communications of the ACM, 2025)
The article argues that sustained federal investment is a strategic necessity—critical not only for continued scientific progress but also for national security, global competitiveness, and the long-term vitality of the U.S. technology ecosystem. The author suggests that federal funding for basic, high-risk computing research has been the driving force behind many of America’s most transformative technologies, including the Internet, modern AI, RISC architecture, Wi-Fi–enabling algorithms, and software-defined networking and that by supporting fundamental inquiry, training new generations of technical talent, and enabling ideas too early or uncertain for private-sector investment, federal agencies create a virtuous cycle that fuels innovation, economic growth, and the emergence of entire industries.